1992
DOI: 10.2135/cropsci1992.0011183x003200040045x
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Alcohols in Endophyte‐Infected Tall Fescue Under Drought

Abstract: Infection of tall fescue (Festuca arundinacea Schreb.) by a fungal endophyte (Acremonium coenophialum Morgan‐Jones & Gains) improves drought tolerance, but the mechanism is unknown. Research was conducted to determine if endophyte‐infected tall fescue subjected to drought stress accumulated sugar alcohols. An infected and uninfected clone of a ‘Kentucky 31’ tall fescue genotype was greenhouse grown in perlite at field capacity or −1.0 MPa for 7 d. Sugar alcohols and other soluble carbohydrates were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 0 publications
2
65
0
Order By: Relevance
“…Most probably the plants infested with N. uncinatum survived the period better due to the symbiont, and thus, there was a higher yield under the conditions enhancing growth, in 2007. The main mechanisms of such an effect of the endophyte are mainly: an increase in the volume of the plant root system, root elongation, earlier and more rapid closing of stomata, accumulation and metabolism of carbohydrates and a greater content of phenolic compounds (Malinowski et al 1997;Elmi and West 1995;Richardson et al 1992). Owing to good growth conditions in 2007, E-plants regenerated and the differences between combinations E+ and E-in 2008, were smaller.…”
Section: Discussionmentioning
confidence: 99%
“…Most probably the plants infested with N. uncinatum survived the period better due to the symbiont, and thus, there was a higher yield under the conditions enhancing growth, in 2007. The main mechanisms of such an effect of the endophyte are mainly: an increase in the volume of the plant root system, root elongation, earlier and more rapid closing of stomata, accumulation and metabolism of carbohydrates and a greater content of phenolic compounds (Malinowski et al 1997;Elmi and West 1995;Richardson et al 1992). Owing to good growth conditions in 2007, E-plants regenerated and the differences between combinations E+ and E-in 2008, were smaller.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the endophytic alkaloids peramine, lolitrem B, and janthitrems were highly correlated with fungal biomass as well (Rasmussen et al, 2007). Mannitol is a very common polyol in fungi (Lewis and Smith, 1967) and has been described earlier to accumulate in endophyte-infected tall fescue (Richardson et al, 1992) and ryegrass plants (Harwood, 1954). Although mannitol has been implicated as an osmoprotectant in the resurrection plant Myrothamnus flabellifolia (Bianchi et al, 1993), a study in N. coenophialum-infected tall fescue indicates that mannitol levels are not increased by drought (Richardson et al, 1992).…”
Section: Mannitol and Fungal Biomassmentioning
confidence: 90%
“…Mannitol is a very common polyol in fungi (Lewis and Smith, 1967) and has been described earlier to accumulate in endophyte-infected tall fescue (Richardson et al, 1992) and ryegrass plants (Harwood, 1954). Although mannitol has been implicated as an osmoprotectant in the resurrection plant Myrothamnus flabellifolia (Bianchi et al, 1993), a study in N. coenophialum-infected tall fescue indicates that mannitol levels are not increased by drought (Richardson et al, 1992). A recent review (Solomon et al, 2007) also questions this role for mannitol and concludes that the role and requirement of mannitol seem to differ depending on the fungus.…”
Section: Mannitol and Fungal Biomassmentioning
confidence: 99%
“…Experimental details for their use, laboratory manipulation, toxin analysis, and plant interaction are contained therein (8,(21)(22)(23)(24)(25)(26)(27).…”
Section: Experimental Microorganisms and Approachesmentioning
confidence: 99%